Behavioral Response, Fumigation Activity, and Contact Activity of Plant Essential Oils Against Tobacco Beetle (Lasioderma serricorne (F.)) Adults - Ren, Yanling; Wang, Tao; Jiang, Yingjie; Chen, Ding; Zuo, Wenyu; Guo, Jianjun; Jin, Daochao (Frontiers in Chemistry, 2022)
Tobacco beetle (Lasioderma serricorne (F.)) is one of the main storage pests that harm tobacco leaves. The current control methods mainly include physical control, chemical control, and biological control, but they all have their own disadvantages. In this study, 22 kinds of plant essential oils in grapefruit, peppermint, juniper, eucalyptus, myrrh, lemon grass, geranium, tea tree, cypress, citronella, patchouli, benzoin, rosemary, cinnamon, clary sage, bergamot, mastic, ginger, rose hydrosol, cedar, thyme, and basil, respectively, are selected to explore their behavioral responses against L. serricorne adults using a glass Y-tube olfactometer. The behavioral responses results show that 17 kinds of essential oils in eucalyptus, basil, grapefruit, cypress, mastic, peppermint, patchouli, juniper, geranium, thyme, benzoin, lemon grass, cinnamon, ginger, rosemary, clary sage, and citronella can avoid L. serricorne adults, while 5 kinds of essential oils in tea tree, rose hydrosol, myrrh, bergamot, and cedar of can attract L. serricorne adults. Especially, essential oils in eucalyptus and grapefruit can avoid L. serricorne adults at 1 μL/L with the repellent rates of 94.67% and 94.56%, respectively. Meanwhile, 17 kinds of essential oils which can avoid L. serricorne adults are selected to determine their fumigation activity against L. serricorne adults using the erlenmeyer flask test method, and bioassay results show that, after 72 h of treatment, 5 kinds of plant essential oils in rosemary, eucalyptus, basil, citronella, and geranium show excellent fumigation activity against L. serricorne adults with the mortality rates of 100.00%, 95.29%, 95.29%, 94.12%, and 91.76%, respectively, and their LD50 of the contact activity against L. serricorne adults determined using the leaf-dipping method are 3.60, 3.49, 8.90, 6.70, and 7.80 μL/L, respectively. Our results show that plant essential oils could be develop as the environmentally friendly insect control agents.